Allocation of production and injection in areas of commingled production of two or more reservoirs - R. A. Neshchadimov (Наука. Инновации. Технологии)
The need for separation of oil production, liquid and injection arises at fields where two or more formations are combined into one production facility. Correct allocation of production and injection is necessary for localization of residual reserves and assignment of geological and technical measures aimed at their development. The occurrence of errors at the stage of allocation of production and injection leads to uncertainty in localization of residual reserves, which causes low efficiency of geological and technical measures. For this reason, improving the technique for production and injection allocation in commingled production is an urgent task. The materials used for the study were publications in national and foreign scientific and technical sources related to the separation of production and injection, as well as field data and the results of interpretation of field geophysical studies. In order to improve the technique of separation of production and injection, based on the studied national and foreign experience in solving this problem, the most significant factors to be taken into account in the allocation technique were identified. The study proposes an improved technique for allocation of oil, liquid production and injection during joint development of two formations with account of changes in reservoir pressure, perforation intervals, reservoir productivity, propagation of hydraulic fracturing cracks, as well as different nature of formation flooding. The improved technique has been tested at one of the fields in Western Siberia, where two oil reservoirs have been combined for commingled production. The allocation of oil, liquid production and injection in each well for the entire development period has been performed, the development of reserves by reservoirs has been determined, and the presence of unproductive injection in the area of the technique testing has been established.